(untitled) (Journal of Economic Research & Business Administration, 2017)
Trends in the dynamic development of the financial market makes it necessary to explore the many aspects of finance, including investment in securities. The investment process is one of the complex mechanisms in finance. The difficulty lies in the fact that the parameters and investment criteria are always changing and filled with new forms. The article deals with the investment in assets to generate income and minimize risk. On the basis of the study identified the main investment principles of R.Dalio and U.Baffet. The principles R.Dalio considered investment rules based on four economic factors and individual portfolio taking into account these factors. Also, the economist uses the principle of rebalancing, which is a key element in investing. Everyone knows Warren Buffett has many rules of investing, buyout is very useful not only for private investor but also for large institutional investors. The proposed principles Dalio and Buffett’s investment rules will help private investors in the efficient operation of the financial market.